Das jüdische Altenhaus am Grindel/Die jüdische Geschichte des heutigen katholischen Studentenwohnheims Franziskus-Kolleg in Hamburg im 19. Jahrhundert - Lange, Alissa (Hamburger Historische Forschungen, 2008)
The third volume of the "Hamburger Historische Forschungen" (Hamburg Historical Studies) deals with the so far hardly known history of a house in the Grindelviertel in Hamburg. Today it is home to the Catholic student dormitory Franziskus-Kolleg. In the late 19th century it was a Jewish dormitory for elderly people in need. The history of this Jewish old people's home is described for the first time in this well-founded study from its foundat ion until the turn of the century. It thus contributes to the study of the diverse Jewish life in Hamburg.